EFFECTS OF CASH MANAGEMENT ON FINANCAIL PERFORMANCE OF PRIVATE SECONDARY SCHOOLS IN MUGADISHU-SOMALIA. - NUR MOHAMED, ABSHIR; OMAR, NIGIB (IJRDO - Journal of Business Management, 2016)
This study tried to investigate how private schools can properly manage their cash in an “optimal way”. it was reported that among the problems that affect private schools in Mogadishu leading to their failure were negative cash management and poor record keeping at International Education. This leaves the gap that is poorcash collection fees from the students and payment to pay teachers, operating expenses and miscalculate the actual time to collect student’s overdue accounts receivables, in which the researcher caused to in investigate about the impact of cash management on profitability of Private schools with a case study of secondary schools. The general objective of the study is to investigate the effects of cash management on profitability of private schools in Mogadishu, Somalia. Researcher was used descriptive and statistical analysis with the help of the SPSS computer package to analyze the data. The researcher recommends that the Private schools should adopt cash management strategy to increase their control to collections fees as it was founded that cash collection positively affects the financial performance of Private Schools to improve their competitiveness and financial performance. The findings indicated that cash management has high effect on financial performance of Private secondary schools in Mogadishu, Somalia. The results revealed that all variables were significant in explaining Financial Performance of Private secondary schools in Mogadishu, Somalia